WATER ENVIRONMENT IMPROVEMENT BY INVESTIGATING RIVER WATER QUALITY - Supit, Cindy J. (TEKNO, 2015)
Investigating river water quality is an important research topic in the integrated basin management and will providea new approach to water environment improvement. In this study, the observed environment done with the analyzing river water quality. From the observation, the results show that the water quality of Kase River basin is generally as good. The conditions in the periods after dam construction indicate that river water quality impairment do exist, but not much and still meet the environmental qualification. The replenishment of Kase River Dam reservoir with the Hokuzan dam reservoir in the basin has less affected to change the water quality along the river due to the good implementation of pollution control in this area. Key words : observed environment, river water quality